Effects of the gap size on the flow pattern maps in a mini-gap annular channel - Pipathattakul, Manop; Mahian, Omid; Dalkilic, Ahmet Selim; Wongwises, Somchai (ELSEVIER SCIENCE INC, 2014)
An experimental study has been performed to examine the effects of gap size on the flow pattern maps of air-water two-phase flow inside a mini-gap annular channel with inclination angles (theta) of 0 degrees, 30 degrees, and 60 degrees. The tests are conducted for three different sizes of the inner diameters (D-i) of the concentric annular test section-namely 8, 10, and 11 mm-while the outer diameter is equal to 12.5 mm. The flow pattern maps are presented for various types of flow including plug flow, slug flow, annular/slug flow, annular flow, bubbly/plug flow, bubbly/slug-plug flow, churn flow, and dispersed bubbly flow, regarding the alteration of gap sizes and inclination angles. According to the experimental conclusions, the angle of inclination and the various gap sizes are influential in the transition of flow regimes. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Two-phase flow; Mini-channel; Narrow annular channel; Flow pattern; Pressure drop; Void fraction; 2-PHASE FLOW; PRESSURE-DROP; LIQUID FLOW; Thermodynamics; Engineering; Physics